2019
DOI: 10.21680/2446-7286.2018v4n2id16844
|View full text |Cite
|
Sign up to set email alerts
|

Perfil Epidemiológico Da Mortalidade Neonatal No Rio Grande Do Norte-Brasil: Um Estudo De Base Secundária

Abstract: Introdução: Considerada um indicador da condição de vida e saúde da população, a mortalidade neonatal, responsável por 60% a 70% dos óbitos infantis nas últimas décadas ocorrem principalmente até o 6º dia de vida. Objetivo: Analisar o perfil epidemiológico da mortalidade neonatal no estado do Rio Grande do Norte numa série histórica de 2005 a 2014. Métodos: Estudo de série temporal e descritiva, com abordagem quantitativa baseado em dados secundários extraídos dos arquivos da Secretaria de Saúde do Rio Grande … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…10 An Apgar score lower than 7, especially in the 5th minute, increases the chances of neonatal mortality.17 Several studies have shown that different Apgar scores were associated with neonatal death. [23][24][25] In our series, it was observed that children born with an Apgar score in the 5th minute of life < 3 were 5.75 times more likely to die when compared to those born with a higher score. The Apgar score < 7, has the risk of developing brain damage, especially if it is < 3 at the 10th minute, has an increased risk of developing cerebral palsy.…”
Section: Discussionmentioning
confidence: 99%
“…10 An Apgar score lower than 7, especially in the 5th minute, increases the chances of neonatal mortality.17 Several studies have shown that different Apgar scores were associated with neonatal death. [23][24][25] In our series, it was observed that children born with an Apgar score in the 5th minute of life < 3 were 5.75 times more likely to die when compared to those born with a higher score. The Apgar score < 7, has the risk of developing brain damage, especially if it is < 3 at the 10th minute, has an increased risk of developing cerebral palsy.…”
Section: Discussionmentioning
confidence: 99%
“…As causas de morte neonatal do atual estudo corroboram, em parte, com os dados obtidos no estado do Alagoas, no período de 2008 a 2017, onde as principais causas de morte foram o desconforto respiratório do recém-nascido (19,6%), a septicemia bacteriana do recém-nascido (16,6%) e os transtornos relacionados a gestação de curta duração e baixo peso ao nascer não classificados em outra parte (5,7%) (ARAÚJO et al, 2020). Já em outro estudo do ano de 2014, no estado do Rio Grande do Norte, predominou nos óbitos neonatais o baixo peso ao nascer (74,30%) (SOUZA et al, 2018). A principal hipótese para uma correspondência incompleta das fontes citadas com este trabalho é a presença de disparidades regionais entre as localidades, as quais podem explicar os diferentes desfechos.…”
Section: Página | 14unclassified